Respiratory health, occupation and the healthy worker effect. (10th February 2020) - Senthilselvan, A; Coonghe, W V L; Beach, J
Abstract: Background: Workers are exposed to physical, chemical and other hazards in the workplace, which may impact their respiratory health. Aims: To examine the healthy worker effect in the Canadian working population and to identify the association between occupation and respiratory health. Methods: Data from four cycles of the Canadian Health Measures Survey were utilized. The current occupation of employed participants was classified into 10 broad categories based on National Occupation Category 2011 codes. Data relating to 15 400 subjects were analysed. Results: A significantly lower proportion of those in current employment than those not in current employment reported respiratory symptoms or diseases or had airway obstruction. Similarly, those currently employed reported better general health and had greater mean values for percent-predicted forced vital capacity (FVC), forced expiratory volume in one second (FEV1 ), forced expiratory flow between 25% and 75% of FVC (FEF25–75% ) and FEV1 /FVC ratio. Among males, females and older age groups, significant differences were observed for almost all the respiratory outcomes for those in current employment. Those in 'Occupations unique to primary industry' had a significantly greater likelihood of regular cough with sputum and ever asthma and had lower mean values of percent-predicted FEV1 /FVC and FEF25–75% than those in 'Management occupations'. Those in 'Health occupations' had the highest proportion of current asthma. Conclusions: Participants in current employment were healthier than those not in current employment providing further support for the healthy worker effect. Those in 'Occupations unique to primary industry' had an increased risk of adverse respiratory outcomes and reducing workplace exposures in these occupations has the potential to improve their respiratory health.